Case report: Anisakiasis causing acute dysentery in Malaysia - Amir, A.; Ngui, Romano; Wan Ismail, W.H.; Wong, Kum Thong; Ong, J.S.K.; Lim, Yvonne Ai Lian; Lau, Yee Ling; Mahmud, Rohela (American Society of Tropical Medicine and Hygiene, 2016)
Human anisakiasis is a zoonosis acquired by eating raw or undercooked infected seafood. Herein, we report a case of acute dysentery caused by anisakiasis in a 64-year-old man in Malaysia. A colonoscopy was performed and a nematode larva was found penetrating the mucosa of the ascending colon. Bleeding was observed at the site of penetration. Y-shaped lateral epidermal cords were seen from the cross section of the worm, which is a prominent feature of Anisakis larva. Molecular analysis using polymerase chain reaction of cytochrome oxidase 2 (cox2) gene confirmed the specimen to be larva of Anisakis simplex.